TRANSLATION SHIFT ANALYSIS OF ADJECTIVE PHRASE FOUND IN “RED NOTICE MOVIE 2021” - Sugiantari, Ni Putu Anggi; Utami, Ni Made Verayanti; Permana, I Putu Andri (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2023)
The goals of this study is (1) to identify the different types of adjective phrase translation shifts and (2) to analyzes how the translation equivalent of adjective phrase appears in the subtitle Red Notice Movie 2021 translation shift. The theory from Catford (1965) was used to analyze the varieties of translation shift of adjective phrase translation shifts, while the theory from Bell (1991) was used to analyze the translation equivalent. This study used observation to collect data and qualitative descriptive analysis to analyze the data. Red Notice 2021 was used as a data source. The result of this study got 64 data for the total in the types of translation shift are 23 level shifts, 11 structure shifts, 9 class shifts, and 21 unit shifts, except intra-system shift. Meanwhile, the translation equivalent results are 25 fully equivalent, 33 meaning decreases, 1 meaning increase, and non-equivalent. 4 different meanings, 1 meaningless Level shifts are the most common, and class shifts are the least common. Meanwhile, decreased meaning is the most common type of translation equivalent, increased meaning is the least data in partial equivalent, and no meaning is the least data in non-equivalent. Moreover, translation shifts are required to address these issues and to serve as a strategy for forming the equivalent. Keywords: Translation Shift, Translation Equivalent, Adjective Phrase